Employment of Funds of Excellence against Community Enrichment Activities for the Suppression of Stunters - Alifiya Nisaul Latifah; Yuni , Kusnul Ciptanila (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2024)
President's Decree No. 72 of 2021 on the Acceleration of Stunting Decline states that in order to create healthy, intelligent and productive human resources, with the achievement of sustainable development goals, accelerated stunting decrease action is carried out. The government is providing welfare funds in each welfare area to be managed by the government of the village and used for the purpose of the welfare of the community. Stunting rebellion is on the budget of the welfare fund on the community empowerment program. The purpose of the author making the scientific work is to analyze the richness funds that are focused on stunting deterrence. Research uses qualitative methods with discourse analysis techniques and interview techniques. The sample of the research was a warrior's wreck, a social and empowerment sex head, a wealthy treasurer, an asshole of wealth and a team leader for accelerating stunting reduction in wealth. The results of the research show that the wealth of the Kulon soldiers has a budget and has already realised 76% of the budget to support the government's efforts in stopping stunts. The conclusion and suggestion for the soldier's well-being is to maximize the realization of the budget for the next year with the aim of reducing the number of stunting news significantly.